Forecasting Subnational Monthly Births and Deaths using Seasonal Time Series Methods - Bravo, Jorge Miguel (2019)
Bravo, J. M., & Coelho, E. (2019). Forecasting Subnational Monthly Births and Deaths using Seasonal Time Series Methods. In Evidence-based territorial policymaking: formulation, implementation and evaluation of policy: 26th APDR Congress Proceedings (pp. 1079-1088). Associacao Portuguesa para o Desenvolvimento Regional (APDR).